Researcher attitudes to offset agreements for OA publishing - Francke, Helena (Septentrio Conference Series, 2018)
Watch the VIDEO. The Swedish government has expressed an intention to move towards open access (OA) to publications based on publicly funded research in Sweden. As part of fulfilling this intention, the Bibsam Consortium, working on behalf of a number of Swedish universities, government agencies, and research institutes, has started to include OA in their negotiations with publishers. One consequence is that Bibsam has followed other international actors and entered into a number of offset agreements. The first of these agreements was Springer Compact, which runs from July 2016 to December 2018. The implementation and consequences of this agreement are being investigated at the request of Bibsam, and this presentation builds on findings from this investigation. Offset agreements are presented as one possible road ahead, a temporary one, in the transition towards OA to scholarly publications. A number of factors, including costs and the speed of flipping hybrid journals to full OA, will determine the success of such agreements. The attitudes of the researchers – the authors of the publications – are also key in determining the outcome. This presentation reports on findings from a questionnaire submitted by 375 first authors of articles covered by the Swedish Springer Compact agreement. It will present the authors’ attitudes to OA, to the Springer Compact agreement, and to future similar agreements. The study shows that only about one quarter of respondents knew about the agreement before submitting their work. A majority would not have paid article processing charges (APC) for their article had APCs not been covered by the agreement. Many are generally positive to OA publishing, however. When asked what they think about agreements such as Springer Compact, three quarters wrote in free-text answers that it is “good”, “very good” or “excellent”. Respondents express both appreciation of the easy process and a relief over not having to find funding for OA. Some respondents were more tentative, saying that they appreciate OA, but that their opinion about the agreement depends on the cost. Non-profit solutions to academic publishing or alternative methods to achieving OA were also mentioned as desirable. A small number of respondents would prefer the traditional subscription model. Yet, the vast majority of respondents say they would like to see similar agreements with other publishers. The answers to the questionnaire show that these researchers are very positive to having their work published OA if it is not associated with costs, limitations, or other hassles for the researcher. That is, if publishing remains no more problematic than in the subscription system, researchers see many benefits with OA. However, there is a minority which expresses ideological hesitation. From this, universities and funders can learn the value of facilitating OA publishing for the individual researcher, but also that many researchers will expect agreements to be economically feasible and that there is a potential to engaging researchers even more in the discussion of future solutions.